Fragmentos Florestais Urbanos: Importância, Ameaças e Desafios - Fernandes, Maria Emília de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present study has as its central theme the Urban Forest Fragments - UFFs, considering as such the Conservation Units, Permanent Preservation Areas, and Green Areas located in an urban matrix. These fragments (all located in urban areas but given different names according to their purposes of use) are crucial for the local ecological balance, but still little studied and usually targets of attacks by new modalities and versions of laws and regulations labeled as ecological or sustainable, but which basically aim to facilitate the process of vegetation suppression to the detriment of the expansion of the urban matrix and other casuistic interests. As the main objective of the study, it was sought to point out the importance of conservation and maintenance of UFFs, the socioeconomic relevance of these areas, as well as the main threats and challenges related to their perpetuation within the urban environment. For that, referenced bibliography, legislations applied to the subject were used, as well as a SWOT analysis (acronym in English which, in Portuguese, means Strengths, Weaknesses, Opportunities, and Threats). As a result, the functionalities – in the form of ecosystem services – of urban forest fragments were highlighted, and how these can help to mitigate typical urban problems, such as heat islands, floods, atmospheric pollution, noise, among others. In addition, the social and economic benefits promoted by these remnants were pointed out, such as the generation of employment, income from tourism, and the promotion of environmental education. As a way of summarizing the main difficulties and virtues (both internally and externally) related to these areas, a framework was prepared in the form of SWOT analysis. We can conclude that, despite the efforts that have already been made on the subject, much remains to be done in relation to the protection of UFFs, especially in times when the advance of urbanization and, consequently, of vegetation suppression, are taking place.

O presente estudo possui como temática central os Fragmentos Florestais Urbanos – FFUs, considerando como tal as Unidades de Conservação, Áreas de Preservação Permanente e Áreas Verdes localizadas em matriz urbana. Estes fragmentos (todos localizados em áreas urbanas, mas que recebem nomes distintos conforme suas finalidades de uso) são cruciais para o equilíbrio ecológico local, mas ainda pouco estudados e geralmente alvos de ataques de novas modalidades e versões de leis e regimentos rotulados como ecológicos ou sustentáveis, mas que no fundo visam facilitar o processo de supressão de vegetação em detrimento da expansão da malha urbana e outros interesses casuísticos. Como objetivo principal do trabalho, buscou-se pontuar a importância da conservação e manutenção dos FFUs, a relevância socioeconômica destas áreas, bem como as principais ameaças e desafios relacionados à sua perpetuação dentro do meio urbano. Para tanto, utilizou-se bibliografia referenciada, legislações aplicadas ao tema, e também análise SWOT (acrônimo em inglês que, em português, significa Forças, Fraquezas, Oportunidades e Ameaças). Como resultado, foram sinalizadas as funcionalidades – no formato de serviços ecossistêmicos – dos fragmentos florestais urbanos, e como essas podem auxiliar na mitigação de problemáticas tipicamente urbanas, tais como ilhas de calor, enchentes, poluição atmosférica, ruído, entre outros. Além disso, apontou-se os benefícios sociais e econômicos promovidos por esses remanescentes, tais como a geração de emprego, o ganho com turismo e a promoção de educação ambiental. Como forma de sintetizar as principais dificuldades e virtudes (tanto internamente quanto externamente) relacionadas à essas áreas, elaborou-se um quadro na modalidade de análise SWOT. Em síntese conclusiva, apesar dos esforços que já vêm sendo dispostos sobre a temática, percebe-se que muito se há a fazer em relação à proteção dos FFUs, sobretudo em tempos nos quais o avanço da urbanização e, consequentemente, da supressão vegetal, se mostra cada vez mais imponente.
Urban Forest Fragments: Importance, Threats and Challenges
Keywords: Socioeconomic factors; Urban environment; Forest fragments; Environmental services; Fatores socioeconômicos; Meio urbano; Fragmentos florestais; Serviços ambientais